Reversible SAHH inhibitor protects against glomerulonephritis in lupus-prone mice by downregulating renal α-actinin-4 expression and stabilizing integrin-cytoskeleton linkage - Shijun He; Xing Liu; Zemin Lin; Yuting Liu; Lei Gu; Hu Zhou; Wei Tang; Jianping Zuo (Arthritis Research & Therapy, 2019)
Abstract Background Glomerulonephritis is one of the major complications and causes of death in systemic lupus erythematosus (SLE) and is characterized by glomerulosclerosis, interstitial fibrosis, and tubular atrophy, along with severe persistent proteinuria. DZ2002 is a reversible S-adenosyl-l-homocysteine hydrolase (SAHH) inhibitor with potent therapeutic activity against lupus nephritis in mice. However, the molecular events underlying the renal protective effects of DZ2002 remained unclear. This study is designed to uncover the molecular mechanisms of DZ2002 on glomerulonephritis of lupus-prone mice. Methods We conducted a twice-daily treatment of DZ2002 on the lupus-prone NZB/WF1 mice, and the progression of lupus nephritis and alteration of renal function were monitored. The LC-MS-based label-free quantitative (LFQ) proteomic approach was applied to analyze the kidney tissue samples from the normal C57BL/6 mice and the NZB/WF1 mice treated with DZ2002 or vehicle. KEGG pathway enrichment and direct protein-protein interaction (PPI) network analyses were used to map the pathways in which the significantly changed proteins (SCPs) are involved. The selected proteins from proteomic analysis were validated by Western blot analysis and immunohistochemistry in the kidney tissues. Results The twice-daily regimen of DZ2002 administration significantly ameliorated the lupus nephritis and improved the renal function in NZB/WF1 mice. A total of 3275 proteins were quantified, of which 253 proteins were significantly changed across normal C57BL/6 mice and the NZB/WF1 mice treated with DZ2002 or vehicle. Pathway analysis revealed that 13 SCPs were involved in tight junction and focal adhesion process. Further protein expression validation demonstrated that DZ2002-treated NZB/WF1 mice exhibited downregulation of α-actinin-4 and integrin-linked kinase (ILK), as well as the restoration of β1-integrin activation in the kidney tissues compared with the vehicle-treated ones. Conclusions Our study demonstrated the first evidence for the molecular mechanism of SAHH inhibitor on glomerulonephritis in SLE via the modulation of α-actinin-4 expression and focal adhesion-associated signaling proteins in the kidney.